KEONG GONDANG PILA AMPULLACEA : MAKANAN DAN REPRODUKSINYA (GASTROPODA : AMPULLARITOAE) - DJAJASASMITA, MACHFUDZ (BERITA BIOLOGI, 1987)
M. DJAJASASMITA. 1987. The apple-snail Pilaampulacea: its food and reproduction (Gastropoda: ampullariidaej. Berita Biologi 3(7) : 342 - 346. The food and reproduction of the apple-snail Pila ampullacea have been studied in the laboratory, reared in aquarium, fed with dead papaya leaves (Carica papaya) and water hyacinths (Eichhomia. crassipes); shrimp crips and fish pellets which are fed by way of trial, were readily eaten.The eggs, 5-10 mm in diameter, are laid in clusters of 15-50 or more, on the aquarium walls about 10 cm off water level. In its natural habitat, in Lake Maja; West Java, the eggs clusters are found stickedon the stems of the kirai palms (Metroxylon rumphii) (which grow densely in the lake) about 75 cm above water level.In the ponds of the Bogor Botanical Garden, the egg cluster were attached on the stems of the aquatic plants (Cyperus papyrus, Hanguana malayana, Sagittaria lancifolia and Thali geniculata) 20-70 cm off the water edge.The egg cluster is covered by a calcareous layer, it is presumed, that this calcareous covering may absorbed dew/rain water, to prevent the eggs desiccating, Some egg clusters laid in the laboratory which are not provided by calcareous layer (it seems due to the physiological disturbance) were desiccating and failed to hatch. The females may deposit 1-2 egg clusters monthly in the rainy season, or may not at,all in the dry season. The peak of the spawning is coincided with the rainy season.